Pengembangan Metode Project Based Learning Untuk Pendidikan Agama Islam Di SDIT MTA Kotabumi Lampung Utara - Amumpuni, Habibah; Azizah, Azizah; Fathir, Fanny Akmal; Alif Prayoga, Ferlian Nur; Sajdah, Meilisa (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2025)
Project-Based Learning (PjBL) is a project-based learning method that encourages students to learn through exploration, collaboration and application of knowledge in completing real projects. The aim of this research is to find out how to develop the Project Based Learning method for Islamic religious education at SDIT MTA Kotabumi North Lampung. This method uses qualitative with a case study approach. Case studies consist of detailed studies, often data, collected from a particular period, phenomenon, and context, with the aim of providing an analysis of the context and process of the study's theoretical inquiry. The researcher collected data using the observation/observation method, the observation carried out by the researcher was a participant observer, which is a direct observation, which means that the researcher directly became a participant in the research. The object observed was the implementation of P5 learning activities as a characteristic of the independent curriculum carried out by students at SDIT MTA Kotabumi, namely 22 Class III students. The results of this research are the development of a Project Based Learning (PjBL) Model for PAI at SDIT MTA Kotabumi which provides a positive response from students in learning, most students are happy and enthusiastic in the learning process.